Syair “Nazam Usiat”: Gaya Bahasa dan Isi - Welmi Dia Wati (Universitas Andalas, 2012)
Nazam Usiat is one of Mesjid Syeikh Sa’id Al-Khalidi Bonjol manuscripts collection. Besides stories, this manuscript contains Islamic advices and azimat. This article describe research result of metaphoric languages style and content analysis of Syair Nazam Usiat. The result shows that this manuscript use metaphor, simile, and unique diction. Otherwise, this text tells about Adam and Eve story, heaven and hell, and several advices in controlling lust.